Using Kolb's Learning Model in Structured Types of Professional Education and Training for Teachers - Močinić, Snježana; Tatković, Sanja (Revija za elementarno izobraževanje, 2021)
The use of Kolb's model enhances the effects of professional developmentbecause the model allows the exchange of concrete experience, reflectiveobservation, abstract conceptualisation and active experimentation, and providesthe connection between theory and practice. The empirical part of this paperanalyses the results of a survey conducted among teachers from Croatian primaryschools regarding the presence of the four stages of Kolb’s learning model instructured types of professional education and training. The survey showsteachers’ dissatisfaction regarding the presence of activities such as reflection onteaching, linking theory to practice and stimulating research activities in teachingpractice.
Keywords: lifelong learning, Kolb's learning model, structured types of learning, professional education and training, teachers